COVID-19-Associated Coagulopathy in the Peripartum Setting: A Case Report - Ashley Allen; Christine Hoang; Roopina Sangha (Thieme Medical Publishers, Inc., 2022)
Sepsis-induced coagulopathy (SIC) scoring and D-dimer can be used to recognize COVID-19-induced coagulopathy, but the utility of these is largely unknown in the peripartum setting and leaves anticoagulation guidance unclear. We present the case of a critically ill postpartum patient with COVID-19 infection. This patient presented with clinical signs of COVID-19 infection and developed acute respiratory failure requiring invasive mechanical ventilation and subsequent cesarean delivery at 34 weeks. She initially improved postoperatively but deteriorated after postoperative day 5. She was found to have a very elevated D-dimer of 58 μg/mL and anticoagulation was escalated to full dosing. She required prolonged mechanical ventilation and deceased after developing gram-positive cocci bacteremia. This case demonstrates that recognition and management of COVID-19-associated coagulopathy can be confusing in the peripartum period and studies are needed to validate D-dimer and SIC scoring in this population of patients.